Measurement of single-diffractive dijet production in proton–proton collisions at √s=8Te with the CMS and TOTEM experiments - KAYA, MİTHAT (My University, 2020)
© 2020, CERN for the benefit of the CMS and TOTEM collaborations.Measurements are presented of the single-diffractive dijet cross section and the diffractive cross section as a function of the proton fractional momentum loss ξ and the four-momentum transfer squared t. Both processes pp→pX and pp→Xp, i.e. with the proton scattering to either side of the interaction point, are measured, where X includes at least two jets; the results of the two processes are averaged. The analyses are based on data collected simultaneously with the CMS and TOTEM detectors at the LHC in proton–proton collisions at s=8Te during a dedicated run with β∗=90m at low instantaneous luminosity and correspond to an integrated luminosity of 37.5nb-1. The single-diffractive dijet cross section σjjpX, in the kinematic region ξ40Ge, and pseudorapidity | η| < 4.4 , is 21.7±0.9(stat)-3.3+3.0(syst)±0.9(lumi)nb. The ratio of the single-diffractive to inclusive dijet yields, normalised per unit of ξ, is presented as a function of x, the longitudinal momentum fraction of the proton carried by the struck parton. The ratio in the kinematic region defined above, for x values in the range - 2.9 ≤ log 10x≤ - 1.6 , is R=(σjjpX/Δξ)/σjj=0.025±0.001(stat)±0.003(syst), where σjjpX and σjj are the single-diffractive and inclusive dijet cross sections, respectively. The results are compared with predictions from models of diffractive and nondiffractive interactions. Monte Carlo predictions based on the HERA diffractive parton distribution functions agree well with the data when corrected for the effect of soft rescattering between the spectator partons.
Keywords: Fizik; Astronomi ve Astrofizik; Temel Bilimler; Mühendislik ve Teknoloji; Physics; Astronomy and Astrophysics; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Mühendislik; Uzay bilimi; ASTRONOMİ VE ASTROFİZİK; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); ENGINEERING; SPACE SCIENCE; ASTRONOMY & ASTROPHYSICS; Mühendislik (çeşitli); Fizik Bilimleri; Fizik ve Astronomi (çeşitli); Engineering (miscellaneous); Physical Sciences; Physics and Astronomy (miscellaneous)